Question
upstudy study bank question image url

For the function \( f \), given below, find the antiderivative \( F \) that satisfies \( F(1)=2 \). \( f(x)=x^{3}-4 x^{-2}+3 \) The antiderivative that satisfies the given condition is \( F(x)=\square \).

Ask by Burns Lane. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The antiderivative \( F(x) \) is \( \frac{x^4}{4} + \frac{4}{x} + 3x - \frac{21}{4} \).

Solution

To find the antiderivative \( F(x) \) of the function \( f(x) = x^3 - 4x^{-2} + 3 \) that satisfies \( F(1) = 2 \), follow these steps: 1. **Find the indefinite integral of \( f(x) \):** \[ F(x) = \int f(x) \, dx = \int \left( x^3 - 4x^{-2} + 3 \right) dx \] 2. **Integrate each term separately:** \[ \begin{align*} \int x^3 \, dx &= \frac{x^4}{4} \\ \int -4x^{-2} \, dx &= -4 \cdot \left( -\frac{x^{-1}}{1} \right) = \frac{4}{x} \\ \int 3 \, dx &= 3x \\ \end{align*} \] 3. **Combine the results and add the constant of integration \( C \):** \[ F(x) = \frac{x^4}{4} + \frac{4}{x} + 3x + C \] 4. **Use the initial condition \( F(1) = 2 \) to solve for \( C \):** \[ \frac{1^4}{4} + \frac{4}{1} + 3(1) + C = 2 \\ \frac{1}{4} + 4 + 3 + C = 2 \\ 7.25 + C = 2 \\ C = 2 - 7.25 = -5.25 = -\frac{21}{4} \] 5. **Substitute \( C \) back into the expression for \( F(x) \):** \[ F(x) = \frac{x^4}{4} + \frac{4}{x} + 3x - \frac{21}{4} \] **Final Answer:** \[ F(x) = \frac{x^4}{4} + \frac{4}{\,x\,} + 3\,x\; -\; \frac{21}{4} \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Mind Expander

To find the antiderivative \( F(x) \), we start by integrating the function \( f(x) = x^3 - 4x^{-2} + 3 \). \[ F(x) = \int (x^3 - 4x^{-2} + 3) \, dx \] Integrating each term separately, we get: \[ F(x) = \frac{x^4}{4} - 4 \cdot \left(-\frac{1}{x}\right) + 3x + C = \frac{x^4}{4} + \frac{4}{x} + 3x + C \] Now we need to determine \( C \) such that \( F(1) = 2 \). \[ F(1) = \frac{1^4}{4} + \frac{4}{1} + 3 \cdot 1 + C = \frac{1}{4} + 4 + 3 + C \] \[ F(1) = \frac{1}{4} + 7 + C = \frac{29}{4} + C \] Setting \( F(1) = 2 \): \[ \frac{29}{4} + C = 2 \] \[ C = 2 - \frac{29}{4} = \frac{8}{4} - \frac{29}{4} = -\frac{21}{4} \] Thus, the antiderivative \( F(x) \) that satisfies \( F(1) = 2 \) is: \[ F(x) = \frac{x^4}{4} + \frac{4}{x} + 3x - \frac{21}{4} \] So we can conclude: The antiderivative that satisfies the given condition is \( F(x) = \frac{x^4}{4} + \frac{4}{x} + 3x - \frac{21}{4} \).

Latest Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy